Concussion in Sports: The Sideline Assessment - Broglio, Steven P. (SAGE Publications, 2009)
CONTEXT: The vast differences between individual athletes makes identifying and evaluating sports-related concussion one of the most complex and perplexing injuries faced by medical personnel. EVIDENCE ACQUISITION: This review summarizes the existing literature supporting the use of a multifaceted approach to concussion evaluation on the sideline of the athletic field. Information was drawn from a PubMed search (MEDLINE) for the terms sport concussion for the most recent and relevant literature. CONCLUSIONS: By using a standardized clinical examination that is supported by objective measures of concussion-related symptoms, mental status, and postural control, the medical professional becomes well equipped to make an informed diagnosis.